КРИСТАЛЛОХИМИЯ СЕЛЕНАТОВ С МИНЕРАЛОПОДОБНЫМИ СТРУКТУРАМИ. IV. КРИСТАЛЛИЧЕСКАЯ СТРУКТУРА ZN(SE04)(H20)2 - НОВОГО СОЕДИНЕНИЯ СО СМЕШАННЫМ КАРКАСОМ ВАРИСЦИТОВОГО ТИПА - Кривовичев С.В. (My University, 2006)
Crystal structure of a new compound Zn(Se04)(H20)2 (orthorhombic, Pbca, a = 9.0411(13), b = 10.246(2), с = 10.3318(15) A, V= 957.1(3) A3) has been solved by direct methods and refined to Д, = 0.033 on the basis of 1076 unique observed reflections with \Fui\ 5: 4<t|Fah|. The structure contains one independent Zn2+ cation coordinated by two water molecules and four oxygen atoms of selenate groups. The only independent (Se04)2_ tetra-hedral oxoanion is tetradentate, i. e. shares corners with four adjacent [Zn2+02(H20)4]2+ octahedra. The structure can be described as consisting of heteropolyhedral sheets parallel to the (001) plane and linked together into a three-dimensional network. The compound belongs to the variscite structure type and is the first structurally characterized selenate of this group.
Keywords: 548.736